FEATURES OF COMPUTED TOMOGRAPHY PARAMETERS OF ANTERIOR HORN OF THE LATERAL VENTRICLE OF BRAIN IN HEALTHY BOYS AND GIRLS WITH VARIOUS SOMATOTYPES - Shevchuk, Yu. G. (Journal of Education, Health and Sport, 2015)
Shevchuk Yu. G. Особливості комп’ютерно-томографічних параметрів передніх рогів бічних шлуночків головного мозку у здорових юнаків і дівчат різних соматотипів = Features of computed tomography parameters of anterior horn of the lateral ventricle of brain in healthy boys and girls with various somatotypes. Journal of Education, Health and Sport. 2015;5(11):356-362. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34098 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A356-362 https://pbn.nauka.gov.pl/works/671001 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015. УДК 616-073.756.8:612.824-053.7:616.853 Особливості комп’ютерно-томографічних параметрів передніх рогів бічних шлуночків головного мозку у здорових юнаків і дівчат різних соматотипів FEATURES OF computed tomography PARAMETERS OF anterior horn of the lateral ventricle OF BRAIN IN HEALTHY boys and girls WITH various SOMATOTYPES Ю. Г. Шевчук Yu. G. Shevchuk Вінницький національний медичний університет імені М.І.Пирогова, м. Вінниця Vinnitsa National Medical University named after Pirogov, Vinnitsa Summary In the boys and girls of different somatotypes defined features computed tomographic parameters of the anterior horn of the lateral ventricles of the brain. In boys endo-mesomorph found significantly greater length of the anterior horn of the right and left lateral ventricles, compared with boys of mesomorphic somatotype and middle intermediate and longer distance between the front horns of the lateral ventricles in young men with an average somatotype intermediate compared with endo-mesomorph. In girls mesomorph found significantly greater length of the anterior horn of the right and left lateral ventricles compared to girls endo and endo-mesomorph. The rest of the parameters of the anterior horns of the lateral ventricles both in boys and girls with different somatotypes had no significant differences or trends to performance. Кey words: boys, girls, somatotype, brain, anterior horn, lateral ventricles, computed tomography. Резюме У юнаків і дівчат різних соматотипів визначено особливості комп’ютерно-томографічних параметрів передніх рогів бічних шлуночків головного мозку. У юнаків ендо-мезоморфів встановлено достовірно більшу довжину переднього рогу правого і лівого бічних шлуночків порівняно із юнаками із мезоморфним і середнім проміжним соматотипом та більшу відстань між передніми рогами бічних шлуночків у юнаків із середнім проміжним соматотипом порівняно із ендо-мезоморфами. У дівчат мезоморфів встановлено достовірно більшу довжину переднього рогу правого і лівого бічних шлуночків порівняно із дівчатами ендо-та ендо-мезоморфами. Решта параметрів передніх рогів бічних шлуночків як у юнаків, так і у дівчат різних соматотипів не мали достовірних або тенденцій до відмінностей показників. Ключові слова: юнаки, дівчата, соматотип, головний мозок, передні роги, бічні шлуночки, комп’ютерна томографія. Резюме ОСОБЕННОСТИ КОМПЬЮТЕРНО-ТОМОГРАФИЧЕСКИХ ПАРАМЕТРОВ передних рогов боковых желудочков ГОЛОВНОГО МОЗГА У ЗДОРОВЫХ ЮНОШЕЙ И ДЕВУШЕК РАЗНЫХ соматотипов. У юношей и девушек разных соматотипов определены особенности компьютерно-томографических параметров передних рогов боковых желудочков головного мозга. У юношей эндо-мезоморфов установлено достоверно большую длину переднего рога правого и левого боковых желудочков по сравнению с юношами с мезоморфным и средним промежуточным соматотипом и большее расстояние между передними рогами боковых желудочков у юношей со средним промежуточным соматотипом по сравнению с эндо-мезоморфами. У девушек мезоморфов установлено достоверно большую длину переднего рога правого и левого боковых желудочков по сравнению с девушками эндо- и эндо-мезоморфами. Остальные параметры передних рогов боковых желудочков как у юношей, так и у девушек разных соматотипов не имели достоверных или тенденций к различиям показателей. Ключевые слова: юноши, девушки, соматотип, головной мозг, передние рога, боковые желудочки, компьютерная томография.